PECULIARITIES OF SOCIAL AND PSYCHOLOGICAL SUPPORT FOR PARENTS RAISING CHILDREN WITH SPECIAL EDUCATIONAL NEEDS (Psychology Travelogs, 2023)
The article examines the theoretical aspects of of the peculiarities of social and psychological support for families raising children with special educational needs. The article clarifies the essence of the concepts of "support", "social and psychological support", "social and psychological support for parents raising children with special educational needs".The authors of the article argue that social and psychological support for parents is a dynamic, holistic and active process that combines a single interconnection of components as a system of comprehensive care.The article describes the concepts that highlight the experiences of parents raising children with special educational needs: "the concept of regret", "the concept of chronological sadness".The article discusses the areas of social and psychological support for parents raising children with special educational needs: shifting their attention to themselves and then to their child; adaptation to a stressful situation; moving away from the feeling of guilt; reducing anxiety and stress; developing skills of a realistic and adequate attitude towards their child; providing emotional and psychological support to parents.The authors of the article investigate the stages, ways and methods of providing social and psychological support to parents raising children with special educational needs.
Keywords: children with special educational needs; families with children with special educational needs; interpersonal relationships; social and psychological support